Organic agriculture development in Vietnam in the new era: current situation, opportunities, and challenges - Nguyen Hong Son; Ngo Duc Minh (Journal of State Management, 2025)
Organic agriculture is regarded as a sustainable pathway, contributing to environmental protection, improving the quality of agricultural products,and meeting the growing demands of both domestic and international markets. Despite its significant potential, the development of organic agriculture in Vietnam still faces numerous limitations - from producers' limited awareness and small-scale production to the lack of acomprehensive support mechanism. This paper examines the theoretical and practical foundations of organic agriculture, evaluates the current state of its development in Vietnam, and identifies the challenges and difficulties associated with its implementation. On this basis, the study proposes several solutions to promote sustainable development of organic agriculture, aligning with natural conditions, socio- economic contexts, and the requirements of international integration.